Continued purchase intention in live-streaming shopping: Roles of expectation confirmation and ongoing trust - Hsiu-Chia Ko; Shun-Yuan Ho (Cogent Business & Management, 2024)
Consumer demands have recently shifted toward an efficient shopping experience, which is a process that minimizes the time, money, effort, and cognitive load required by consumers to make purchase decisions and complete transactions. This shift has prompted social commerce platforms to invest in innovative business models aimed at maintaining customer loyalty. This study investigated how live-streaming shopping (LSS) aligns with changing consumer demands for efficient shopping experiences. We extended the Expectation Confirmation Model by including utilitarian value and ongoing trust as variables to examine their influence on continued purchase intention. We administered a questionnaire survey to experienced LSS users, which yielded 292 valid responses. Partial least squares structural equation modelling was performed on the collected responses to evaluate the proposed research models. The results revealed that postpurchase confirmation of the coviewers' positive word of mouth significantly increases perceived LSS value; this highlights the vital role of real-time social interactions in LSS. Moreover, we observed that confirmation of the quality of streamer-provided information can maintain ongoing trust; this demonstrates the importance of streamers' ability to leverage real-time video streaming effectively. Our analysis of postpurchase expectation confirmation underscored the importance of reliable streaming and ordering systems for ensuring LSS satisfaction among consumers. The results also indicated that perceived LSS value and ongoing trust significantly enhance consumers' LSS satisfaction, which increases their continued purchase intention. This study contributes to the literature on LSS by demonstrating how the efficient characteristics of LSS align with evolving consumer demands and behaviours.
Keywords: 650; Social commerce; live-streaming shopping (LSS); expectation confirmation model (ECM); ongoing trust; continued purchase intention; utilitarian value